Comparative Study on the Carcass Traits of Commercial Native Chicken, Backyard Native Chicken, Commercial Broiler and Spent Layer Chicken - Sathishkumar, R.; Kulkarni, V. V.; Chandirasekaran, V.; Vasan, P.; Muthulakshmi , M. (Journal of Meat Science, 2019)
To study the effect of class of chicken on the carcass traits an experiment was conducted on 12 birds of either sex in each commercial native chicken, backyard native chicken, commercial broiler and spent layer chicken. Birds were slaughtered by Jatka method and carcass traits were recorded. Live weight, dressed carcass weight, dressing percentage and meat: bone ratio was significantly higher (P<0.01) in commercial native chicken, commercial broiler and backyard native chicken than spent layer chicken. Meat bone ratio was significantly (P<0.01) higher in commercial broiler than backyard native chicken. Yield of giblet was significantly higher (P<0.01) in backyard native chicken than the other three groups. Influence of sex was significant in all the parameters and higher values were recorded in males than females for dressing percentage and meat bone ratio. The dressing percentage and meat bone ratio was higher in the commercial broiler.